Three-Point Bending Response of Corrugated Core Metallic Sandwich Panels Having Different Core Configurations – An Experimental Study - Zurnaci, E.; Gokkaya, H.; Nalbant, M.; Sur, G. (Engineering, Technology & Applied Science Research, 2019)
Bending response of corrugated core metallic sandwich panels was studied experimentally under three-point bending loading. Two different core configurations were used: the corrugated monolithic core and the corrugated sliced core. The trapezoidal corrugated cores were manufactured from aluminum sheets via a sheet metal bending mould. After the sandwich panel samples were prepared, they were subjected to three-point bending tests. The load and displacement responses of the sandwich panels having different core configurations were obtained from the experimental testing. The influence of the core configuration on the three-point bending response and failure modes was then investigated. The experimental results revealed that the corrugated sliced core configuration exhibited an improved bending performance compared to the corrugated monolithic core configuration.